New you a center for plastic and cosmetic surgery - Ong, Colleen Ann L.; Espina, Mary Ann A. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
New you is a study which primarily aims to formulate a design solution for a one-stop medical facility dedicated to Plastic and Cosmetic Surgery. The facility seeks to provide patients with beautification of a holistic nature -- taking into account not only the body, but also the mind and the spirit. The study examines the current state of the Medical Tourism industry, as well as existing trends, particularly in the field of Plastic Surgery. Based on research, the Philippines does have the capacity to become a leader in Medical Tourism -- considering its natural resources, highly skilled manpower, and cost competitiveness. Findings have then been used to assess where existing facilities fall short. These problems were then addressed through a proposed architectural design solution that seeks to give the local Medical Tourism industry a much-needed boost.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Health facilities -- Designs and plans; Medical tourism